Eye and brain : the psychology of seeing - Gregory, R. L. (Richard Langton), 1923- (Oxford : Oxford University Press, 1994)
Looks at how we see brightness, movement, colour and objects.
Originally published: London : Weidenfield and Nicholson, 1990. - Previous edition: 1977.
P.B
P.B
Includes bibliographical references (pages .241-250) and index.
Keywords: Visual perception; Fisiologia geral; Physiologische Psychologie; Visual perception; Visuelle Wahrnehmung; Vision, Ocular; Visual Perception; Hersenen; Visuele waarneming; Humans -- Visual perception